PERBEDAAN KADAR VITAMIN C PLASMA ANTARA IBU HAMIL DENGAN KETUBAN PECAH DINI PRETERM DAN TANPA KETUBAN PECAH DINI PRETERM - , Martini Fairus, Prof. Dr. Djaswadi Dasuki, MPH,PhD,Sp.OG (K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Premature rupture of membranes (PROM) is rupture of membranes without labor followed in pregnancy at term or preterm.Â PROM affects 10-20% of all deliveries, and is associated with increased morbidity and neonatal and maternal mortality worldwide.Â PROM cause preterm labor resulting in the birth of low birth weight babies are a major cause of infant mortality.The research objective was to determine differences in plasma levels of vitamin C among pregnant women with preterm PROM and preterm PROM without.Â  Determine the correlation between vitamin C and preterm premature rupture of membrane. The design of observational analytic study with case control study design, in Bantul District Hospital Panembahan Senopati from November 2011 until February 2012. Technique Nonprobability sampling, type of consecutive. Sample size was calculated to test the hypothesis against the odds ratios for case-control study, obtained a sample of 40 people, 20 cases and 20 controls without preterm PROM.. Total plasma vitamin C levels examined in the laboratory of biochemistry FK-UGM, 2.4 dinitrophenylhydrazine calorimetric method. Normal total plasma concentrations of â¥ 0.6 mg / dl. Data were analyzed by univariate, bivariate with independent t test, chi square test, fisher's exact test, multivariate analysis with logistic regression. The results univariate analysis of mean plasma levels of vitamin C in the group the preterm PROM and without the preterm PROM was 0.9 vs 1.1. The results obtained by independent t test p = 0.24 (IK95% -0.55-0.14). The results of logistic regression test values obtained for the levels vitamin C plasma OR 2.80, (IK95% 0.38-20.79), anemia OR 6.42, (IK95% 0.89-46.45) infections OR 6.54 (IK95% 0.32-21.72) PROM history previous values obtained OR 2.65, (IK95% 0.32-21.72). Conclusions plasma vitamin C levels did not differ between pregnant women with preterm premature rupture of membranes and without preterm premature rupture of membranes. Low plasma vitamin C levels are not associated with the incidence of premature rupture of membranes.